Length-weight relationship and condition factors of Channa striata in Tanjung Haloban village, Labuhanbatu - Asri Asyhari; Rusdi Machrizal (Jurnal Biolokus: Jurnal Penelitian Pendidikan Biologi dan Biologi, 2022)
This study aims to determine about length-weight relationship and condition factors of Channa striata in Tanjung Haloban village, Bilah Hilir District, Labuhanbatu Regency. The study was conducted from October to December 2021. Sampling of snakehead fish (C. striata) had done in Tanjung Haloban village. Measurement of the length and weight of snakehead fish (C. striata) was carried out in the ecology laboratory of the Faculty of Teacher Training and Education, Universitas Labuhanbatu. The tools used in this study among others rods, ruler, scales, calipers, buckets. Sampling is carried out for three months with fishing gear. The length-weight relationship can be analyzed using the linear allometric model (LAM) equation. Based on the results of the analysis of the relationship in the length of the snakehead fish weight (C. striata) shows that the results of measuring the length of the snakehead fish weight can be known that male and female snakehead fish have a negative alomatric pattern with a value of b<3, while the condition factor calculated with relative weight (WR) 100.58 and the fulton condition factor (K) 0.85 is close to 1 which means the condition of the swamp waters of the snakehead fish habitat is in a balance state.